PENGARUSUTAMAAN GENDER (PUG) SEKTOR PENDIDIKAN - Machmud, Fadiah (Eklektika: Jurnal Pemikiran dan Penelitian Administrasi Pendidikan, 2013)
This study was conducted at Education Office in South Sulawesi Province with three main problems, there were: how is the pre-requisite of PUG in Education Office, how is the PUG on the policy planning and the programs, how is the PUG on the implementation programs, activity and the evaluation of the implementation. This study employed qualitative descriptive approach. Data were obtained through interview and the study on Renstra, Renja, the report on the program implementation, and LAKIP. Data analysis was conducted by categorizing the content of the policy into the neutral gender, responsive gender, bias gender, potential responsive gender, and providing reformulation proposal of responsive gender.The result reveals that gender has not succeeded as the mainstream. The pre-requisite of PUG has not been utilized optimally, seemed as an order from the â€œcenterâ€, Pokja PUG has not been institutionalized although its membership from various backgrounds, PUG seems exclusive in PPMK division. The separated data based on gender is a crucial obstacle of gender failure as the mainstream in the planning. Gender perspective has not been explicitly stated in planning due to lack of staff capacity planner and the system and mechanism have not been established wich can enforce the planning staff to be more responsive in working. As a consequence, the implementation of the program and activity are not responsive gender. The output and the target have not specifically showed men and women that it makes it difficult to ensure whether both have the same benefit on the programs. The gender indicator has not been integrated into the performance indicator.